2016
DOI: 10.1111/grs.12119
|View full text |Cite
|
Sign up to set email alerts
|

Morph‐physiological responses of two switchgrass (Panicum virgatum L.) cultivars to cadmium stress

Abstract: Two cultivars of switchgrass, ‘Alamo’ (lowland type) and ‘Cave‐in‐Rock’ (upland type), were used to examine the morph‐physiological responses of plants to different cadmium (Cd) levels under hydroponic condition treated with 0, 10, 20 and 40 μmol L−1 CdCl2 for 2 weeks. The main results showed that both seedlings of ‘Alamo’ and ‘Cave‐in‐Rock’ can survive even in 40 μmol L−1 CdCl2 treatment. However, the growth of the two cultivars was significantly (at least P < 0.05) inhibited by Cd stress. The plant biomass, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…2 and 4). For 'Alamo' a higher Cd translocation factor and lower Cd concentration in shoot and root than 'Cave-in-Rock' was consistent with a previous study (Liu et al 2016). Higher biomass and higher Cd amounts in shoots of Alamo than Blackwell was also obtained by Chen et al (2011), who suggested that Alamo had greater potential than Blackwell for Cd phytoextraction.…”
Section: Discussionsupporting
confidence: 89%
“…2 and 4). For 'Alamo' a higher Cd translocation factor and lower Cd concentration in shoot and root than 'Cave-in-Rock' was consistent with a previous study (Liu et al 2016). Higher biomass and higher Cd amounts in shoots of Alamo than Blackwell was also obtained by Chen et al (2011), who suggested that Alamo had greater potential than Blackwell for Cd phytoextraction.…”
Section: Discussionsupporting
confidence: 89%
“…The seeds of ‘ Alamo ’ (lowland type) were used in this study. Alamo plants were cultured as described by Liu [ 14 ]. Briefly, the plants were grown in half-modified Hoagland solution (containing 5 mmol L −1 Ca[NO 3 ] 2 , 5 mmol L −1 KNO 3 , 1 mmol L −1 KH 2 PO 4 , 2 mmol L −1 MgSO 4 , 25 μmol L −1 Fe-EDTA-Na 2 , 50 μmol L −1 H 3 BO 3 , 0.3 μmol L −1 CuSO 4 ·5H 2 O, 4.5 μmol L −1 MnSO 4 ·H 2 O, 3.8 μmol L −1 ZnSO 4 ·7H 2 O and 0.1 μmol L −1 [NH 4 ] 6 Mo 7 O 24 ·4H 2 O).…”
Section: Methodsmentioning
confidence: 99%
“…Switchgrass, a warm-season C 4 perennial grass, can be grown on marginal lands that are usually unsuitable for food crops [ 12 , 13 ]. This plant was found to accumulate Cd efficiently due to its high biomass production [ 14 ]. In addition, switchgrass is also regarded as an important energy crop for biofuel production.…”
Section: Introductionmentioning
confidence: 99%
“…The Bc09-inoculated plants had significantly ( p < 0.05) higher TF (13%), whereas the mixed-inoculated plants had significantly ( p < 0.05) (54%) lower TFs compared to the noninoculated Cd-control plants (Figure 2D). It is known that if the Cd concentration of at least 100 mg Kg −1 is accumulated [37] and the TF is greater than 1, then a plant is considered as hyper-accumulator [38]. In our study, the TF was less than 1 in both PGPB-inoculated and noninoculated Cd-control plants.…”
Section: Resultsmentioning
confidence: 62%